PROGRAM READING SAFARI UNTUK MENINGKATKAN MINTA BACA SISWA MADRASAH IBTIDAIYAH PEJOK BOJONEGORO - Denny Nurdiansyah; Emilia Fatmawati; Lilis Dwi Agustin; Habibah Zulfana Lailiyah (Yayasan Education and Social Center, 2022)
Children in Madrasah Ibtidaiyah Islamiyah in Pejok Village are less interested in reading because most of them are more interested in online games than reading books. In addition, there are also who like reading because of coercion from their parents. Another problem, access to reading at MI is not sufficient so that students are not interested in going to the library because the room less supportive. The purpose of activity is to implement the Reading Safari Program by adding a reading studio program to increase students' reading interest. The implementation method is carried out by a series of reading activities that include the role of students in getting used to reading and telling what they read. Results of the service obtained are that students can take part in activities in an orderly and smooth manner and then get some book and socialize benefits of reading. In addition, this activity also contributed a collection of books to the MI Library. The conclusion obtained that MI Islamiyah students in Pejok village actually have a good interest in reading but the reading books provided by the school are less varied so that collection of books in the school library needs to be added